THE INFLUENCE OF PRODUCT DIVERSITY, BRAND IMAGE, LIFESTYLE AND PROMOTION IN IMPLEMENTING CONSUMER BUYING INTEREST AT SALON SANS WELLNEESS BATAM - Firmanda, Rizki; Izjumadillah, Izjumadillah; Roslinawati, Dina; Sardi, Muhammad; Hendra, Hendra; Kurniawan, Harie (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This study aims to analyze the relationship between product diversity, brand image, lifestyle, and promotion with consumer purchase interest at Salon Sans Wellness Jodoh Batam, both individually and collectively. The population of this research consists of all consumers of Salon Sans Wellness Jodoh Batam, totaling 400 in January. A sample of 80 respondents was selected using the accidental sampling technique. The results indicate a significant positive influence of product diversity, brand image, lifestyle, and promotion on consumer purchase interest. Based on multiple regression analysis, brand image is found to be the most influential factor on consumer purchase interest. Additionally, the research instruments met the validity and reliability requirements. These findings highlight the importance of brand image in shaping consumer purchase interest.